Monitoramento da Bacia Hidrográfica do Rio Santa Rita em Marmeleiro, Paraná - Flessak Junior, Paulo (2023)
The quality of a river’s water is influenced by the activities carried out along its water-shed, including agricultural, urban, and small industrial activities that make it vulnerable to degradation and pollution. From this, the present work aims to monitor the water quality, evaluating physicochemical, microbiological parameters, presence of estrogen hormones, and toxicity of the Santa Rita River, located in the municipality of Mar-meleiro - PR, its main source is in the rural area, passing through the urban area and has the exutório on the left bank of the Marmeleiro River. Water samples were col-lected throughout the four seasons of 2022, at five different points of the river, making a correlation with the use and occupation of the soil along the watershed. The presence of oils and greases was observed in the four collections from point one to point four, with the highest value observed at the river’s source. BOD values above the limit es-tablished by CONAMA 357/2005 were observed: in the first collection at point two, in the second collection at points two to four, in the third collection at points two to five, and for the fourth collection at points two, three, and five. As for pH, only in the third collection was a value of 4.93 observed, at the river’s source, outside the limits of 6 to 9 established by CONAMA resolution 357/2005. Four of the four hormones studied were detected in concentrations considered high in the samples from all points col-lected in three of the four seasons evaluated: autumn, winter, and spring. Regarding the ecotoxicological tests, samples two and four from the fourth collection had escape rates of 60 and 80% respectively, indicating that they were toxic. The PCA analysis showed a positive correlation of root growth with turbidity, total nitrogen, color, and PO4, and in the fourth collection, a correlation of the toxicity found in the escape test with BOD, BQO, pH, turbidity, and the presence of Estradiol. Pointing to a relationship between these data and the use and occupation of the watershed observed in the maps. The sub-basin corresponding to point 1 (P1), the source of the Santa Rita river, despite being located in the rural area of the municipality of Marmeleiro - PR, is formed by 38% urbanized area and 42% area for agriculture, which favors water contamina-tion. Sub-basin 5, corresponding to the entire Santa Rita River basin, with 11.2 km², the use and occupation of the soil observed on the map is 23% urbanized area and 32% is made up of vegetation and 45% agricultural area. The overall view of the basin shows that both in rural and urban environments the presence of humans and their activities of use and occupation of the soil as well as the characteristics of rainfall sea-sonality interfere with water quality, making clear the importance of controlling anthro-pogenic activities and monitoring water parameters along the basin for the preservation of its quality, biodiversity, and human health.